Adsorption and detoxification of pharmaceutical compounds from wastewater using nanomaterials: A review on mechanism, kinetics, valorization and circular economy. (15th December 2021) - Singh, Simranjeet; Kumar, Vijay; Anil, Amith G.; Kapoor, Dhriti; Khasnabis, Sutripto; Shekar, Shweta; Pavithra, N.; Samuel, Jastin; Subramanian, S.; Singh, Joginder; Ramamurthy, Praveen C.
Abstract: Antibiotics overuse, inappropriate conduct, and discharge have led to adverse effects on various ecosystems. The occurrence of antibiotics in surface and drinking water is a matter of global concern. It is responsible for multiple disorders, including disruption of endocrine hormones and high chronic toxicity. The hospitals, pharmaceutical industries, households, cattle farms, and aquaculture are the primary discharging sources of antibiotics into the environment. This review provides complete detail on applying different nanomaterials or nanoparticles for the efficient removal of antibiotics from the diverse ecosystem with a broader perspective. Efforts have been made to focus on the degradation pathways and mechanism of antibiotic degradation using nanomaterials. More light has been shed on applying nanostructures in photocatalysis, which would be an economical and efficient solution. The nanoscale material or nanoparticles have incredible potential for mineralizing pharmaceutical compounds in aqueous solutions at low cost, easy handling characteristics, and high efficacy. Furthermore, nanoparticles can absorb the pharmaceutical by-products and wastes at a minimum cost as they can be easily recycled. With the increasing number of research in this direction, the valorization of pharmaceutical wastes and by-products will continue to expand as we progress from old conventional approaches towards nanotechnology. The utilization of nanomaterials in pharmaceutical wastewater remediation is discussed with a major focus on valorization, energy generation, and minimization and its role in the circular economy creating sustainable development. Graphical abstract: Image 1 Highlights: Various treatments methods and their mechanism to mitigate antibiotic contaminated wastewater are explored. Nanoparticles have incredible potential for mineralizing pharmaceutical compounds. Adsorption and regeneration studies using nanoparticles are crucial to select feasible antibiotic wastewater remediation techniques. Valorization, energy generation and recovery would impact circular economy in sustainable pharmaceutical wastewater management.